Genetic parameters estimation for egg quality traits of four chicken breeds using a full diallel cross - Teshome, Philimon; Goshu, G.; Esatu, Wondmeneh; Dessie, Tadelle (Springer, 2025)
This study aimed to estimate heterosis effects (He), general combining ability (GCA), specific combining ability (SCA), reciprocal effects (RE), and maternal effects (Me) for egg quality traits in a 4 × 4 diallel cross involving four chicken breeds: Improved Horro (H), Sasso (S), Potchefstroom Koekoek (K), and Dz-white feathered (D). A total of 480 eggs from 4 purebreds and 12 crossbreds were evaluated for traits like egg weight (EWT), egg length (EL), egg width (EW), shell weight (SWT), shell thickness (ST), shell ratio (SR), albumen height (AH), albumen width (AW), yolk height (YH), yolk width (YW), yolk weight (YWT), yolk ratio (YR), and hugh unit (HU). Results showed positive He for most traits. GCA were significant (p < 0.001) for EWT, EL, EW, AW, YW, YWT, and YR. Variation due to SCA was high (p < 0.001) for all traits. K×S cross showed positive RE for EWT and AW. D×S cross had the highest positive RE for ST. Both additive and non-additive gene actions play significant roles in controlling egg quality traits. EWT and YWT were primarily influenced by additive genetic effects, while EL, EW, ST, and YR were dominated by non-additive effects. Me exhibited significant variation across genotypes for most traits. In conclusion, future breeding strategies aiming for additive genetic gains should prioritize breeds S and K in recurrent selection programs, while crosses such as S×D, K×D, and H×K can be utilized to exploit heterosis for targeted traits. Additionally, maternal lines should be optimized to reduce Me and enhance overall performance.